2020
DOI: 10.1038/s41598-020-69926-8
|View full text |Cite
|
Sign up to set email alerts
|

Fermi-crossing Type-II Dirac fermions and topological surface states in NiTe2

Abstract: Transition-metal dichalcogenides (TMDs) offer an ideal platform to experimentally realize Dirac fermions. However, typically these exotic quasiparticles are located far away from the Fermi level, limiting the contribution of Dirac-like carriers to the transport properties. Here we show that NiTe 2 hosts both bulk Type-II Dirac points and topological surface states. The underlying mechanism is shared with other TMDs and based on the generic topological character of the Te p-orbital manifold. However, unique to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 29 publications
3
48
0
Order By: Relevance
“…Those nontrivial band crosses form topological insulator state or topological Dirac semimetal state, contingent upon the same or different angular momentums of the crossing bands respectively. We note that the band inversion along k z is not unique to iron-based superconductors, it occurs ubiquitously in the 1T phase of transition metal dichalcogenides (such as PtTe 2 , PdTe 2 , and NiTe 2 ) [107][108][109]. In principle, topological band structure can be produced in all the iron-based superconductors under sufficient tuning.…”
Section: Topological Band Structurementioning
confidence: 92%
“…Those nontrivial band crosses form topological insulator state or topological Dirac semimetal state, contingent upon the same or different angular momentums of the crossing bands respectively. We note that the band inversion along k z is not unique to iron-based superconductors, it occurs ubiquitously in the 1T phase of transition metal dichalcogenides (such as PtTe 2 , PdTe 2 , and NiTe 2 ) [107][108][109]. In principle, topological band structure can be produced in all the iron-based superconductors under sufficient tuning.…”
Section: Topological Band Structurementioning
confidence: 92%
“…Another plausible origin of the FCPM is related to the Zeeman shift of the proximitized topological surface states of NiTe 2 . Previous studies 23,24 have reported the presence of spin-polarized surface states in NiTe 2 that cross the Fermi level. Here we have used ARPES to examine the detailed fermiology of these surfaces states and estimate their Fermi energy and velocity (Supplementary Sections IX and X).…”
mentioning
confidence: 91%
“…NiTe 2 crystallizes in a CdI 2 -type trigonal crystal structure with the space group P 3m1, which is centrosymmetric 23,24 (Supplementary Section I). This 2D van der Waals material is a type-II Dirac semimetal that hosts several spin-helical topological surface states 23,24 . As discussed later, these surface states play a key role in the JDE.…”
mentioning
confidence: 99%
“…Among the family of TMD materials, the layered binary tellurides of Co and Ni (CoTe 2 and NiTe 2 ) have been reported many times for their different physical properties. ,− Especially, since the discovery of 1 T -NiTe 2 as a topological material having Dirac semimetallic properties with the Dirac fermions close to the Fermi energy, it has provided a new platform to study the type-II Dirac. …”
Section: Introductionmentioning
confidence: 99%